Cellular reprogramming by transcription factor engineering - Tsang, Jason CH; Gao, Xuefei; Lu, Liming; Liu, Pentao (Current opinion in genetics & development, 2014)
Summary diagram showing the modulation of gene expression by designer transcription factors generated by different platforms. TALE: Transcription activator-like Effector; ZFE: Zinc Finger Effector; CRISPRE: Clustered Regularly Interspaced Short Palindromic Repeats Effector. Recent researches have identified multiple transcription factors as permissible reprogramming factors to pluripotency and lineage switching. The current standard strategy by ectopic factor overexpression however has intrinsic limitations in studying the reprogramming mechanism. There is a growing interest in engineering novel chimeric reprogramming factors and applying designer transcription factors technology to improve reprogramming efficiency and dissect the process of endogenous pluripotency network reactivation. Here, we provide a concise review on the latest progress in studying cellular reprogramming by transcription factor engineering.